Предмет: Математика,
автор: theshool
(3y-6) (4y-2) - (2y-9) (6y+5) - 1 =0
помогите с этим пожалуйста
Ответы
Автор ответа:
0
(3у-6)(4у-2)-(2у-9)(6у+5)-1=0
3у(4у-2)-6(4у-2)-2у(6у+5)-9(6у+5)-1=0
12у²-6у-24у²-10у+54у-45-1=0
12у²-6у-24у²-10у+54у=45+1
-12у²+38у=46
я не знаю
3у(4у-2)-6(4у-2)-2у(6у+5)-9(6у+5)-1=0
12у²-6у-24у²-10у+54у-45-1=0
12у²-6у-24у²-10у+54у=45+1
-12у²+38у=46
я не знаю
Похожие вопросы
Предмет: Литература,
автор: asemgul293
Предмет: История,
автор: sparku259
Предмет: Окружающий мир,
автор: egorovau166
Предмет: География,
автор: валькири1
Предмет: Математика,
автор: vitkova